Risk factors for the development of acquired myopia in children - Tsybulska, T. E.; Pashkova, E. E.; Цибульська, Таміла Євгенівна; Пашкова, Олена Єгорівна (My University, 2018)
The article we present the results of a factor analysis of the development of acquired myopia in children. Data of 80 children (160 eyes) with acquired myopia of weak degree and 20 children (40 eyes) without ophthalmic pathology were analysed. The conducted factor analysis revealed 3 main factors that were designated as an «anatomically-constitutional» (48.9% of the total dispersion), “hereditary” (7.6% of the total dispersion) and “morphometric” (7.1% of the total dispersion). It was established that the factor load of more than 0.7 was introduced by the variables of corneal refractive force (-0.882), axial eye length (-0.765), corneal curvature radius (0.748), corneal diameter (0.827), reserve of relative accomodation (-0.721), as well as the stage of connective tissue dysplasia (0,810). The factor load of heredity variable was (0.817), the factor load of the variable of peripapillary layer of nerve fibers was (-0.855). The obtained factor analysis data can be used in individual prediction of the probability of development of myopia in children.
Keywords: myopia; risk factors; development; factor analysis; children